The Exploring Credibility Challenges of Malaysian Online News Portals - LIANG, NG WEI; TIUNG, LEE KUOK (Indonesian Journal of Economics, Social, and Humanities, 2024)
This study was meant to explore the students' perception of the credibility of Malaysian online news portals using the method of in-depth interviews and focus group discussions (FGD). The results of the study reveal that the proliferation of technologies such as social media and internet accessibility has greatly facilitated university students' access to online news portals. Individuals are seeking up-to-date information more than ever, due to the convenience of technology. Mainstream, alternative, and independent news portals each have distinct impacts on students. Key factors contributing to these credibility issues include information-seeking behaviour, convenience, confirmation bias, and social interaction. Perceptions of credibility vary depending on the type of news portal in the eyes of university students which could be driven by ideology, prejudice, and bias. However, convenience and credibility theme explain why online news portals are often criticized for their lack of credibility in the eyes of university students. Many students perceive clickbait headlines as a major issue with Malaysian online news portals, often finding discrepancies between headlines and the actual content of articles. Incomplete information and journalists' reluctance to address sensitive issues are also significant concerns for students when selecting online news portals. Bias and credibility issues on online news portals often manifest in political and racial controversies. Students also mentioned the 3R issues during the interviews. Despite these concerns, online news portals remain the primary source of information for university students. Overall, the credibility issues have eroded students' confidence in the reliability of online news.